Epidemiologia da sífilis congênita, sífilis em gestantes e fatores associados ao óbito infantil pela doença, Betim, Minas Gerais, 2010 A 2018 - Cristiane Campos Monteiro (2022)
The epidemiology of syphilis in Brazil is characterized by an increase in incidence, hospitalization and mortality rates. Congenital syphilis causes serious complications to the fetus, society and family and for the health systems. This scenario points to the need to improve the response of the surveillance system and health services in the early detection and adequate treatment of pregnant women and partners, as well as the identification of the most vulnerable areas and populations. This study aims to analyze the epidemiological situation and subregistration of congenital syphilis and in pregnant women, infant deaths related to the disease and the spatio-temporal distribution of congenital syphilis in the municipality of Betim, Minas Gerais (MG), registered in the Sistema de Agravos de Notificação (SINAN), Sistema sobre Mortalidade (SIM) and Sistema sobre Nascidos Vivos (SINASC), from 2010 to 2018. An historical cohort study was carried out. Database linkage was used estimate the number of cases of the disease and deaths from the pairing of the three systems and exclusion of duplicities, as well as to identify causes associated with the occurrence of infant death. Poisson regression was performed to assess the association between death from congenital syphilis and maternal and child factors. In order to identify vulnerability, cases of congenital syphilis were mapped by the Planning Unit using the standard ellipse technique to show their distribution. The case map was superimposed on the stratified areas in the municipality's Social Vulnerability Index. There were 411 cases of syphilis in pregnant women and 289 cases of congenital syphilis were confirmed. Death occurred in 32 children: six after birth, eight abortions and 18 stillbirths. The detection rate of syphilis in pregnant women was 1.7 / 1,000 live births in 2010 and 19.7 / 1,000 live births in 2018; the incidence rate of congenital syphilis was 1.7 / 1,000 live births in 2010 and 10.5 / 1,000 live births in 2018. Most pregnant women were young (24.2%) up to 19 years old; 47.7% brown or black; 42.2% do not had completed high school; 71.6% were diagnosed with syphilis during consultations; 97.9% did not treat it adequately and 88.2% of the partners did not treat. Among children, females represented 49.1%; the diagnosis of a non-treponemal test in peripheral blood was positive for 55.5% of the children. Of the children who died, 71.9% of the mother's non-treponemal test at delivery/curettage showed a titer > 1:8. The data relationship between reported cases in residents of Betim for syphilis in pregnant women (411) and congenital syphilis (289) identified 205 true pairs; with maternal underreporting of 17.2% and child underreporting of 40.9%. The linkage of the syphilis bank in pregnant women (411) with the mortality system for women aged 10 to 49 years (1,264) did not identify deaths, and with the infant mortality system (584) identified three deaths. In the relationship between the congenital syphilis databases (389) and the infant mortality system (584), six deaths were identified. There was a higher risk of death from congenital syphilis in pregnant women who were diagnosed in the first trimester, in children without treatment information in the notification, as well as in the result of the non-treponemal test in peripheral blood and cerebrospinal fluid. Children whose mothers were aged between 20 and 29 years had a 58% lower risk of dying from syphilis (CI 95%). Congenital syphilis cases are concentrated in the regions with Planning Units with the highest vulnerability index. Congenital syphilis cases are concentrated in the regions with Planning Units with the highest vulnerability index. Among the 106 planning units, the directional distribution showed a concentration of cases in six planning units. The findings of this study reinforce that syphilis remains a major public health problem, with a high rate of vertical transmission and occurrence of deaths, indicating inefficiency in the quality of prenatal care and low control measures related to the monitoring and treatment of pregnant women and their partners.